Leadership styles towards employee retention in hotel industry : a study in Sibu Town, Sarawak - Chan, Herbert Geh Ming; Wong, Winnie Poh Ming; Mohd Zainal Munshid Harun, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The nature of leadership itself may influence an individual employee’s intention to leave or remain in the organisation. The present study was carried out to examine the impact of directive, servant, participative, and laissez-faire leadership styles in predicting employee retention among employees working in hotels of Sibu Sarawak. Using Role Theory as the underpinning basic theory, the present study explains the relationship between the chosen variables in the proposed model. A quantitative research design was chosen for this research study. WarpPLS (version 6.0) was employed to perform the Partial Least Square-Structural Equation Modeling (PLS-SEM) estimation procedure to examine the developed direct relationship. The purposive sampling technique was used for data collection. A total of 230 usable questionnaires were collected from employees coming from different levels/department in local hotels. Interestingly, the results showed that two predictive factors emerged from the directive and servant leadership styles, which are prevalent in employee retention in the hotel industry. The result of present study may be informative and act as a basic guideline for the future hotel industry players. Additionally, the research is of theoretical importance as it helps to identify the factors that contribute to hotel employee retention. This study also demonstrates the importance of effective leadership style/leadership behaviour for the retention of talented employees in the hotel industry. Some of the theoretical and practical implications have also been highlighted in the study.